APPLICABILITY OF A HUMAN LACTOFERRIN IN PEDIATRIC PRACTICE - T. E. Borovik; G. V. Yatsyk; L. S. Namazova-Baranova; N. G. Zvonkova; N. N. Semenova; О. L. Lukoyanova; P. E. Sadchikov; I. L. Gol'dman; E. R. Sadchikova; I. А. Belyaeva; T. V. Bushueva (Вопросы современной педиатрии, 2014)
Modern data on efficiency and safety of a recombinant human lactoferrin (hLf) and prospects of its use in pediatric practice are presented in the review of literary data. The unique anti-infectious properties of biologically active protein of the hLf, its high antimicrobic, antiviral, antifungal and anti-parasitic activity are noted. Ability to stimulate natural immunity, to interact with other antimicrobic peptides, in particular, with lysozyme and secretory leukocyte protease inhibitor is analysed. In this regard it is indicated prospects of application of the hLf in treatment of prematurely born and hypotrophic children, patients with chronic nutritional deficiency for the purpose of prevention of infectious diseases and correction of inflammatory changes in the organism of a child, includingacute respiratory virus and enteric infections in children. It is expedient to apply hLf in surgical practice for reduction of a degree of manifestation of the acute pro-inflammatory response, and also for prevention of infectious complications, especially after abdominal operations, in complex treatment of children with a severe generalized infection and multi-organ failure, for prevention of intrahospital nosocomial infections in children hospitals.Key words: children, prematurely born, nutritional deficiency, infections, lactoferrin, recombinant human lactoferrin.